Signal peptide exchange alters HIV-1 envelope antigenicity and immunogenicity - Chitra Upadhyay; Priyanka Rao; Mohammad Amin Behzadi; Roya Feyznezhad; Gregory S. Lambert; Rajnish Kumar; Madhu Kumar; Weiming Yang; Xunqing Jiang; Christina C. Luo; Arthur Nadas; James Arthos; et al. (Frontiers in Immunology)
IntroductionHIV-1 envelope (Env) is the key target for antibodies (Abs) against the virus and thus an important HIV-1 vaccine component. Env is synthesized from a gp160 precursor with a signal peptide (SP) at its N-terminus. This study investigated the influence of the SP on Env antigenicity and immunogenicity.MethodsEnv proteins from two HIV-1 isolates, AA05 and AC02, were analyzed as gp120 and gp160 in their native wild-type (WT) forms and as chimeras with swapped SPs (AA05-02 and AC02-05). The WT and chimeric Env were assessed for antigenicity and glycosylation using monoclonal antibodies (mAbs) and glycan probes. Immunogenicity was tested in mice using three vaccine types: gp120 protein, gp120 DNA+gp120 protein, and gp120 DNA+gp160 DNA.ResultsThe recombinant AC02 gp120 protein was antigenically superior to AA05 as indicated by higher reactivity with most mAbs tested. When SPs were swapped, the antigenicity of the chimeric gp120s (AA05-02 and AC02-05) resembled that of the gp120s from which the SPs were derived; AA05-02 was similar to AC02 and vice versa. Glycan probe reactivity followed a similar pattern: AA05-02 and AC02 showed similar affinity to high-mannose specific mAbs and lectins. Interestingly, the antigenicity of gp160s showed an opposite pattern; membrane-bound gp160 expressed with the AA05 SP (AA05 and AC02-05) showed greater mAb binding than gp160 with the AC02 SP (AC02 and AA05-02). Mice immunized with gp120 protein showed that AA05-02 induced stronger cross-reactive binding Ab responses than AA05 WT, and AC02 elicited stronger responses than AC02-05, indicating AC02 SP enhanced gp120 immunogenicity. However, when DNA vaccines were included (gp120 DNA+gp120 protein and gp120 DNA+gp160 DNA), the use of heterologous SPs diminished the immunogenicity of the WT immunogens. Among the three vaccine regimens tested, only gp120 DNA+gp160 DNA immunization elicited low-level Tier 2 neutralizing Abs, with AA05 WT inducing Abs with greater neutralization capabilities than AA05-02.ConclusionThese data demonstrate that the SP can significantly impact the antigenicity and immunogenicity of HIV-1 Env proteins. Hence, while SP swapping is a common practice in constructing Env immunogens, this study highlights the importance of careful consideration of the effects of replacing native SPs on the immunogenicity of Env vaccines.